EFA6 activates Arf6 and participates in its targeting to the Flemming body during cytokinesis. Issue 11 (18th April 2013) - Ueda, Tomoko; Hanai, Ayako; Takei, Tomomi; Kubo, Keiji; Ohgi, Minako; Sakagami, Hiroyuki; Takahashi, Senye; Shin, Hye-Won; Nakayama, Kazuhisa
Abstract : The small GTPase Arf6 is transiently associated with the ingressing cleavage furrow and subsequently targeted to the Flemming body during cytokinesis, suggesting its activation around the cleavage furrow. Here, we show that EFA6 (exchange factor for Arf6) localizes on the cleavage furrow through its PH domain. Time‐lapse analysis showed that both EFA6 and Arf6 are transiently localized around the ingressing cleavage furrow, but only Arf6 is subsequently targeted to the Flemming body. Expression of an EFA6 mutant suppresses Arf6 recruitment onto the Flemming body. These results suggest that EFA6 participates in activation of Arf6 around the cleavage furrow during cytokinesis. Abstract : Arf6 is required for faithful completion of cytokinesis. Arf6 is activated by EFA6 in the cleavage furrow region during cytokinesis. Activated Arf6 is targeted to the Flemming body through interacting with MKLP1.